2005
DOI: 10.5465/amj.2005.17843939
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Design and Environmental Performance: Clues From the Electronics Industry

Abstract: A congruence model of organizational design suggests that direct reporting relationships between plant managers and environmental quality managers, monetary incentives for environmental performance, and coordination between environmental quality managers and business strategists reduce plant-level toxic emissions. We tested these relationships in a large sample of U.S. electronics facilities. Only a link between plant manager compensation and environmental performance reduced emissions. Subsequent analyses sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
282
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(312 citation statements)
references
References 35 publications
11
282
1
6
Order By: Relevance
“…Empirical findings from six environmentally proactive European firms have shown that employees responded positively with creative ideas in the environmental area if their supervisors encouraged daily praise and company environmental awards (Ramus, 2001;Ramus, 2002;Ramus & Steger, 2000). Russo and Harrison (2005) showed by means of an empirical analysis that when managerial pay is tied to environmental performance, facilities reported improvements in their environmental performance. On the contrary Denton's (1999) survey on the some of the best known pollution reducing companies in the world revealed that rarely are incentives, bonuses, salaries and promotions based on how well environmental goals were met.…”
Section: Rewardsmentioning
confidence: 99%
“…Empirical findings from six environmentally proactive European firms have shown that employees responded positively with creative ideas in the environmental area if their supervisors encouraged daily praise and company environmental awards (Ramus, 2001;Ramus, 2002;Ramus & Steger, 2000). Russo and Harrison (2005) showed by means of an empirical analysis that when managerial pay is tied to environmental performance, facilities reported improvements in their environmental performance. On the contrary Denton's (1999) survey on the some of the best known pollution reducing companies in the world revealed that rarely are incentives, bonuses, salaries and promotions based on how well environmental goals were met.…”
Section: Rewardsmentioning
confidence: 99%
“…Anton et al, 2004;e.g. King and Lenox, 2002;Klassen and Whybark, 1999;Russo and Harrison, 2005). Under the EPA's Emergency-Right-to-Know Provision, industrial facilities with 10 or more full-time employees that release any listed toxic substance in excess of minimum reporting threshold to four different media (namely air, water, land, and underground injection) are required to report the type and amount of emissions to the EPA (EPA, 2002).…”
Section: Independent Variables and Controlsmentioning
confidence: 99%
“…Even though the mainstream RBV focuses on intangibles as a source of competitive advantage, studies adopting the natural view have also supported the notion that intangibles may enhance a firm's responsibility performance (e.g., Arag贸n-Correa and Sharma, 2003). Researchers have studied intangibles such as innovation (e.g., Klassen and Whybark, 1999), human resources (e.g., Russo and Harrison, 2005), corporate reputation (e.g., Strong, Ringer, and Taylor, 2001), and organizational culture (e.g., Howard-Grenville and Hoffman, 2003) and their links to different dimensions of corporate responsibility. RBV scholars have also noted that the relationship between intangibles and performancewhether financial variables or responsibility variables-may operate in reverse.…”
Section: Introductionmentioning
confidence: 99%